2008
DOI: 10.1210/jc.2008-0915
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Androgen Insensitivity of the Fetal, Neonatal, and Early Infantile Testis Is Explained by the Ontogeny of the Androgen Receptor Expression in Sertoli Cells

Abstract: A lack of androgen receptor expression could explain a physiological Sertoli cell androgen insensitivity during fetal and early postnatal life, which may serve to protect the testis from precocious Sertoli cell maturation, resulting in proliferation arrest and spermatogenic development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 173 publications
(113 citation statements)
references
References 19 publications
7
101
0
5
Order By: Relevance
“…Combined with the observations that Sertoli cells do not express ARs during fetal development in the rodent or human (Shapiro et al 2005, Chemes et al 2008, these data indicate that the effects of androgens must be mediated through another testicular cell type in the fetus. Immunohistochemical data suggest that it is mostly PMC (and some interstitial cells) that express the AR in the testis during fetal development (Majdic et al 1995, Shapiro et al 2005, Chemes et al 2008; Fig. 1), and it appears likely that androgen action on the Sertoli cells is mediated through the PMC.…”
Section: Sertoli Cellsmentioning
confidence: 60%
See 1 more Smart Citation
“…Combined with the observations that Sertoli cells do not express ARs during fetal development in the rodent or human (Shapiro et al 2005, Chemes et al 2008, these data indicate that the effects of androgens must be mediated through another testicular cell type in the fetus. Immunohistochemical data suggest that it is mostly PMC (and some interstitial cells) that express the AR in the testis during fetal development (Majdic et al 1995, Shapiro et al 2005, Chemes et al 2008; Fig. 1), and it appears likely that androgen action on the Sertoli cells is mediated through the PMC.…”
Section: Sertoli Cellsmentioning
confidence: 60%
“…PMC express the AR in the adult animal, and recent studies have begun to show how important androgen actions, via the PMC, are for normal adult testicular function (Welsh et al 2009). In the fetus, the PMC are the main cell type expressing the AR (Majdic et al 1995, Shapiro et al 2005, Chemes et al 2008, and Sertoli cell number is reduced in ARKO and Tfm mice (Johnston et al 2004, Tan et al 2005, suggesting a role for the PMC in fetal Sertoli cell development. In PMC-ARKO mice (lacking AR on the PMC only), the testes appear largely normal at post-natal day 12, suggesting that fetal Sertoli cell development is largely unaffected (Welsh et al 2009).…”
Section: Peritubular Myoid Cellsmentioning
confidence: 99%
“…On the other hand, Van Roijen et al (1995) found no evidence supporting the stagedependent immunoexpression of AR in human testes, and none of the publications that have investigated the localization of testicular AR identified specific variations in AR immunoexpression in the six stages of the human spermatogenic cycle (Takeda et al, 1989;Ruizeveld de Winter et al, 1991;Kimura et al, 1993;Iwamura et al, 1994). SCAR immunostaining is also dependent on the primary antibody concentration, which causes different rates of positive staining of Sertoli cells (Suarez-Quian et al, 1999;Chemes et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although clinically unperceivable by palpation, testis size increases in early infancy (Goede et al, 2011) mainly due to the proliferation of Sertoli cells (Nistal et al, 1982;Mü ller & Skakkebaek, 1983) [Figs 1(B) and 2]. Interestingly, the elevated levels of intratesticular testosterone cannot induce meiosis in the foetal and neonatal testis most probably due to the lack of androgen receptor expression in Sertoli cells at those developmental periods (Berensztein et al, 2006;Chemes et al, 2008;Boukari et al, 2009;Rey et al, 2009). Subsequently, the activity of the axis decreases substantially; however, AMH (Aksglaede et al, 2010;Grinspon et al, 2011) and inhibin B production (Bergadá et al, 1999;Andersson & Skakkebaek, 2001) persists being active.…”
Section: Infancy and Childhoodmentioning
confidence: 99%